answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}
3p
Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals". My guess - and it is a guess, is 6*(p + 2) - 2p = 6p + 12 - 2p = 4p + 12 where the + is missing throughout. But it could be 6*(p - 2) - 2p = 6p - 12 - 2p = 4p - 12 where most of the - are missing.
That IS the equation. You may want to write with the equal sign: 6p = 24
To solve this group together the like terms. 7p + -p = 6p Then the answer is 6p -9.
Assuming you mean 7 multiplied by just 2p and assuming that p is a variable then p is calculated by: (7 * 2p) + 3 - 8 = 6p + 29 14p - 5 = 6p + 29 14p - 6p = 29 + 5 8p = 34 p = 4.25
-6p -5 = -9 +8p Add 6p to both sides: -5 = -9 + 14p Add 9 to both sides: +4 = 14p Divide both sides by 14: p =4/14 = 2/7 or 0.2857.. Are you sure that the second term in the equation was -5 and not +5 (as seems more likely)?
Factor x2 plus 12xp plus 36p2 is (x+6p)(x+6p).
algebra8p +4 = 10 +6p+8p - 6p = +10 - 42p = 6p = 3
answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}
-9p + 6p = -3p
3p + 6p = (3 + 6)p = 9p
6p + 12q + 18r = 6 (p + 2q + 3r)
14 + 6p = 6 + 7p 8 = p
3p
17p+17q+p-7q-6p = 12p+17q
8p+4=6p+10 8p-6p=2p 10+4=14 2p=14 p=7